2013
DOI: 10.1080/13548506.2012.722649
|View full text |Cite
|
Sign up to set email alerts
|

Impaired perceptual processing and conceptual cognition in patients with anxiety disorders: A pilot study with the binocular depth inversion paradigm

Abstract: The binocular depth inversion test (BDIT) measures a common illusion of visual perception whereby implausible objects are seen as normal, e.g., a hollow face is perceived as a normal, convex face. Such inversion is frequent, especially for objects with a high degree of familiarity. Under normal conditions, cognitive factors apparently override the binocular disparity cues of stereopsis. This internal mechanism of "censorship" of perception, which balances "top-down" and "bottom-up" processes of perception to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…In a 2012 study, patients with anxiety identified a tendency toward lower risk-taking when making a decision [51,52]. In addition, the function of conceptual cognition decreases in patients with anxiety disorders [53]. These cognitive errors are the reasons for reduced task performance in patients with anxiety [54].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2012 study, patients with anxiety identified a tendency toward lower risk-taking when making a decision [51,52]. In addition, the function of conceptual cognition decreases in patients with anxiety disorders [53]. These cognitive errors are the reasons for reduced task performance in patients with anxiety [54].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy in schizophrenia has been shown to be due to strengthened bottom-up and weakened top-down processing that allows schizophrenia patients to interpret the sensory cues of a hollow face that deviate from stored knowledge of faces being convex as concave (Dima, Dietrich, Dillo & Emrich, 2010;Dima et al, 2011Dima et al, , 2009. Apart from schizophrenic patients, individuals with other psychosis-prone states are also less likely to perceive the hollow-mask illusion, such as cannabis users (Leweke, Schneider, Radwan, Schmidt & Emrich, 2000;Semple, Ramsden & McIntosh, 2003), alcohol withdrawal (Schneider et al, 1996), sleep deprivation (Sternemann et al, 1997), youth at ultra-high risk for psychosis (Gupta et al, 2016), and anxiety patients (Passie et al, 2013). Therefore, disposition of veridical perception of concaveness in faces in the psychotic and propsychotic states mentioned above, could be of use in research aiming to identify susceptibility to mental illness.…”
mentioning
confidence: 99%
“…Esses estudos encontraram um prejuízo na capacidade de alguns grupos específicos de realizarem a inversão visual da profundidade da máscara côncava. Pessoas em privação prolongada de sono apresentaram tal prejuízo (Schneider et al, 1996a;Sternemann, et al, 1997), assim como indivíduos com ansiedade (Passie et al, 2013). A esquizofrenia também têm se mostrado ser um fator limitante da capacidade de perceber a ilusão (Schneider et al, 1996a;Schneider et al 2002;Koethe et al 2009;Dima et al, 2009;Dima et al, 2010;Dima et al, 2011).…”
Section: Ilusões Visuaisunclassified